Sludge biochar-based cementing material for solidifying / stabilizing electrolytic manganese residues and solidifying method

By using sludge biochar-based cementitious material to cure manganese ions in electrolytic manganese slag, the problems of poor curing effect and high cost in the prior art are solved, and the low toxicity curing and resource utilization of electrolytic manganese slag are achieved.

CN119430709APending Publication Date: 2025-02-14CHINA THREE GORGES UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411619112.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art has problems in curing electrolytic manganese slag with poor curing effect, high cost and low resource utilization rate.

Method used

Using sludge biochar based cementitious material as a curing agent, a sludge biochar used to cure electrolytic manganese slag is prepared by mixing iron-rich sludge biochar with silicon-aluminum coupled solid waste and alkaline excitation active material. Base cementitious material.

Benefits of technology

The manganese ions in the electrolytic manganese slag were effectively cured, which reduced leaching toxicity, met the requirements of 2mg/L in the "Comprehensive Sewage Discharge Standard" of GB8978-1996, and significantly reduced costs, consumed bulk solid waste, and promoted electrolysis. The harmless and resource utilization of manganese slag.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430709A_ABST
    Figure CN119430709A_ABST
Patent Text Reader

Abstract

The invention provides a sludge biochar-based cementing material for solidifying / stabilizing electrolytic manganese residue, which is prepared by mixing and stirring sludge biochar, silicon-aluminum coupled solid waste and alkali-activated active material, the silicon-aluminum coupling solid waste accounts for 77%-90%, the sludge biochar accounts for 5%-20%, and the alkaline excitation active material accounts for 3%-5%. Solid waste containing a large amount of silicon, aluminum, calcium and other components is used as a raw material to solidify electrolytic manganese residues, meanwhile, due to the fact that selected sludge is iron-rich sludge, in the product hydration process, a large amount of calcium, silicon and aluminum participate in a reaction, corresponding hydration products such as calcium silicate hydrate and calcium aluminate hydrate are generated, and the effect of solidifying the electrolytic manganese residues is achieved. According to the method, the electrolytic manganese residues are subjected to a reaction with calcium hydroxide, heavy metals in the electrolytic manganese residues are wrapped by generated corresponding hydration products, and manganese in the electrolytic manganese residues can react with the calcium hydroxide, so that free manganese is converted into low-mobility and low-toxicity manganese hydroxide and manganese oxide, and the requirement of 2 mg / L in the GB8978-1996 Integrated Wastewater Discharge Standard is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of harmless treatment and resource utilization of electrolytic manganese slag, and specifically relates to a preparation method and application of a sludge biochar-based binder for solidifying / stabilizing electrolytic manganese slag. Background Art

[0002] Electrolytic manganese slag refers to the waste slag produced in the electrolytic manganese process. Every ton of metallic manganese produced produces about 10 tons of electrolytic manganese slag, which is mainly composed of silicon, calcium, iron, oxygen and sulfur and is weakly acidic. Electrolytic manganese slag has the problem of huge quantity and is not conducive to treatment. So far, the main disposal method is still open-air storage and landfill.

[0003] Many scholars at home and abroad are studying the harmlessness and resource utilization of electrolytic manganese slag. The harmlessness treatment mainly involves solidifying the electrolytic manganese slag. By adding solidifying materials, the heavy metals in the electrolytic manganese slag are wrapped inside to reduce the toxicity. A scholar used electrolytic manganese slag, fly ash, and kaolin as raw materials to prepare electrolytic manganese slag-based polymers, and used NaOH and water glass as alkaline activators to leach out the toxic Cd 2+ and Pb 2+ The concentration is far lower than the limit specified in the national standard. Some scholars use electrolytic manganese slag, red mud and carbide slag as the main raw materials to prepare road base materials. After 7 days of maintenance, the material has the highest unconfined compressive strength and the best durability. The composite material has a good solidification effect on heavy metals. Under the synergistic effect, the hydration reaction is sufficient, thereby producing more hydration products, making the solidification effect better. A scholar used clinker, blast furnace slag and electrolytic manganese slag to prepare cement-based cementitious materials. When the content of electrolytic manganese slag is 15%, the early strength of the cement-based cementitious materials is greatly improved, and the heavy metal content in the leachate is significantly reduced. This is because sulfate accelerates the secondary hydration reaction of blast furnace slag, resulting in the generation of more hydration products, and with the consumption of Ca(OH)2, the pore size becomes smaller and the structure becomes denser. There are many ways to comprehensively utilize electrolytic manganese slag, such as preparing unburned bricks, fertilizers, cement additives, etc. Although many scholars have studied how to solidify heavy metals in electrolytic manganese slag, there are still many problems, such as poor solidification effect, high cost, low resource utilization rate, etc. Therefore, it is urgent to find a new method for solidifying electrolytic manganese slag. Summary of the invention

[0004] In view of the above technical problems, the present invention provides a sludge biochar-based binder for solidifying / stabilizing electrolytic manganese slag. The iron-rich sludge biochar is mixed with silicon-aluminum coupled solid waste and alkaline-activated active materials to form a sludge biochar-based binder curing agent for solidifying manganese ions in the electrolytic manganese slag.

[0005] In order to achieve the above-mentioned purpose, the present invention provides a sludge biochar-based binder for solidifying / stabilizing electrolytic manganese slag, wherein the solidifying agent is composed of the following raw materials in weight percentage: 77%-90% silicon-aluminum coupled solid waste, 5-20% sludge biochar, and 3-5% alkaline activated active material.

[0006] Preferably, the sludge biochar-based binder for solidifying / stabilizing electrolytic manganese slag is composed of the following raw materials in weight percentage: 90% silicon-aluminum coupled solid waste, 5% sludge biochar, and 5% alkaline activated active material.

[0007] Preferably, the sludge biochar is prepared by the following steps: drying and grinding the iron-rich municipal sludge, and then pyrolyzing it at 550-650°C for 80-120 min to obtain the original biochar, adding hydrogen peroxide solution to the original biochar, stirring until the mixture is uniformly mixed, drying the obtained mixture, and then pyrolyzing it again at 550-650°C for 80-120 min to prepare the sludge biochar.

[0008] The iron-rich municipal sludge has an iron content of 20-30%; The mass ratio of the original biochar to the hydrogen peroxide solution is 1:5-10, and the mass concentration of the hydrogen peroxide solution is 10-30%.

[0009] The silicon-aluminum coupling solid waste is a mixture of two or more of incineration slag, nepheline tailings, ceramic slurry, construction waste residue and red mud, which are mixed and calcined at 800-900° C. for 1-2 hours.

[0010] Preferably, the alkaline exciting material includes one or more of carbide slag, sodium aluminate, and sodium hydroxide, and the surfactant includes one or more of sodium dodecylaminopropionate, alkyl dimethyl sulfoethyl betaine, and alkyl dimethyl hydroxypropyl phosphate betaine.

[0011] The present invention also provides a method for preparing a sludge biochar-based binder for solidifying / stabilizing electrolytic manganese slag, comprising the following steps: mixing the sludge biochar with silicon-aluminum coupled solid waste and stirring, and adding alkaline activated active materials to prepare a sludge biochar-based binder curing agent.

[0012] A method for solidifying / stabilizing electrolytic manganese slag with a sludge biochar-based binder, comprising the following steps: The sludge biochar is mixed with electrolytic manganese slag, silicon-aluminum coupling solid waste and alkaline-activated active materials and stirred to obtain a sludge biochar-based binder of solidified / stabilized electrolytic manganese slag.

[0013] The electrolytic manganese slag is original electrolytic manganese slag with a moisture content of 10-16%. It is crushed and sieved. In terms of weight percentage, the electrolytic manganese slag accounts for 60-70% of the total amount of the sludge biochar-based binder.

[0014] The beneficial effects of the present invention are: 1. Solid waste containing a large amount of silicon, aluminum, calcium and other components is used as raw material to solidify electrolytic manganese slag. At the same time, because the selected sludge is iron-rich sludge, a large amount of calcium, silicon and aluminum participate in the reaction in the hydration product process to generate corresponding hydration products, such as hydrated calcium silicate, hydrated calcium aluminate, etc. The corresponding hydration products will wrap the heavy metals in the electrolytic manganese slag. At the same time, the manganese in the electrolytic manganese slag will react with calcium hydroxide, so that the free manganese is converted into low-mobility and low-toxic manganese hydroxide and manganese oxide, thereby meeting the 2mg / L requirement in GB8978-1996 "Comprehensive Sewage Discharge Standard".

[0015] 2. Since biochar has the characteristics of large specific surface area and high porosity, it will absorb some water during the stirring process, and then release it during the curing process, so that the hydration products increase, thereby reducing the leaching toxicity. At the same time, due to the small particle size of biochar, it plays a micro-aggregate effect, further reducing the leaching toxicity. During the pyrolysis process of biochar impregnated with hydrogen peroxide solution, the hydrogen peroxide adsorbed in the biochar is decomposed into gas by heat and escapes, thereby increasing the specific surface area and pore size of the biochar. The activation of hydrogen peroxide causes oxygen-containing groups on the surface of the biochar to adsorb some free manganese ions, thereby reducing the overall leaching toxicity. At the same time, the iron ions in the biochar react with hydrogen peroxide to generate ferrous ions, which then participate in the hydration reaction to generate hydration products such as hydrated calcium ferrite. Some free iron ions react with hydroxide to generate iron hydroxide colloid. The hydration products and colloids form an overall spatial network structure to wrap the manganese in the electrolytic manganese slag, so that it will not easily leak into the surrounding environment in the form of leachate, thereby reducing the overall leaching toxicity of the solid body.

[0016] 3. Silicon-aluminum coupled solid wastes such as incinerator slag, nepheline tailings, ceramic mud, red mud, etc. are mixed with alkaline activated materials such as biochar, carbide slag, sodium aluminate and sodium dodecylaminopropionate to make a curing agent to solidify the electrolytic manganese slag, which greatly reduces the cost and consumes a large amount of solid waste. At the same time, it reduces the threat of electrolytic manganese slag to the surrounding environment and human health, and makes the electrolytic manganese slag harmless and resource-based, alleviating the pressure of large-scale storage of electrolytic manganese slag.

[0017] 4. The leaching toxicity of the solidified electrolytic manganese slag is lower than the first-level limit requirement in "GB 8978-1996 Wastewater Discharge Standard" and meets the relevant standards. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1This is the SEM image of the cured product of Example 1.

[0019] Figure 2 This is a CT cross-sectional view of the solidified body of Example 1.

[0020] Figure 3 This is a physical picture of Example 1.

[0021] Figure 4 This is the nitrogen adsorption and desorption and pore size diagram of biochar. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It is worth noting that the following embodiments are only preferred embodiments of the present invention and should not be understood as limiting the present invention. The protection scope of the present invention shall be based on the contents recorded in the claims. Any modification or replacement made by those skilled in the art to the technical solution of the present invention without creative work shall fall within the protection scope of the present invention.

[0023] Electrolytic manganese slag: taken from a manganese company, its main components are as follows (%):

[0024] Incineration slag: taken from an incineration plant, its main components are SiO2 accounting for 40%, Al2O3 accounting for 35%, and CaO accounting for 20%; Nepheline tailings: taken from a certain enterprise, its main components are SiO2 accounting for 43%, Al2O3 accounting for 30%, and CaO accounting for 10%; Ceramic slurry: taken from a certain enterprise, its main components are SiO2 accounting for 70% and Al2O3 accounting for 20%; Red mud: taken from an aluminum enterprise, its main components are CaO accounting for 40%, SiO2 accounting for 20%, Al2O3 accounting for 15%, and Fe2O3 accounting for 15%; Carbide slag: taken from a chemical enterprise, its main component is Ca(OH)2 accounting for more than 85%; Sludge: taken from the secondary sedimentation tank of a sewage treatment plant, its main components are as follows (%):

[0025] Example 1 A sludge biochar-based binder for solidifying / stabilizing electrolytic manganese slag, the formula is 90% silicon-aluminum coupling solid waste, 5% sludge biochar, and 5% alkaline excitation active material; wherein the silicon-aluminum coupling solid waste is a mixture of incineration slag, nepheline tailings, ceramic slurry, and red mud in a mass ratio of 4:2:1:3, the alkaline excitation active material is carbide slag and sodium metaaluminate, the mixing ratio is 6:4, the surfactant is sodium dodecylaminopropionate, and the ratio of alkaline excitation active material to surfactant is 7:3. The preparation method is: (1) First, the above-mentioned sludge was selected, dried at 100-105°C, ground by a planetary vibration mill and passed through a 200-mesh sieve, the treated dry sludge was placed in a tubular furnace and pyrolyzed at 550°C for 80 min to obtain the original biochar SBC, the prepared original sludge biochar was mixed with hydrogen peroxide solution at a mass ratio of 1:5, the mass concentration of the hydrogen peroxide solution was 15%, and stirred for 3 hours. The obtained mixture was dried and placed in a tubular furnace, and pyrolyzed at 550°C for 60 min to obtain the target sludge biochar.

[0026] (2) The sludge biochar is mixed with electrolytic manganese slag, silicon-aluminum coupled solid waste and alkaline activated active materials and stirred to solidify / stabilize the electrolytic manganese slag.

[0027] Table 1 Changes in pore structure of SBC before and after H2O2 modification

[0028] It can be seen from Table 1 that the specific surface area, average pore size and porosity of SBC modified by H2O2 increase significantly.

[0029] Example 2 A sludge biochar-based binder for solidifying / stabilizing electrolytic manganese slag, the formula is 90% silicon-aluminum coupling solid waste, 3% sludge biochar, and 5% alkaline excitation active material; wherein the silicon-aluminum coupling solid waste is a mixture of incineration slag, nepheline tailings, ceramic slurry, and red mud in a mass ratio of 4:2:1:3, the alkaline excitation active material is carbide slag and sodium metaaluminate, the mixing ratio is 6:4, the surfactant is sodium dodecylaminopropionate, and the ratio of alkaline excitation active material to surfactant is 7:3. The preparation method is: (1) First, the iron content of the selected original sludge is higher than 20%. The sludge is dried at 100-105°C, ground by a planetary vibration mill and passed through a 200-mesh sieve. The treated dry sludge is placed in a tubular furnace and pyrolyzed at 550°C for 80 min to obtain original biochar. The prepared original sludge biochar is evenly mixed with a hydrogen peroxide solution at a mass ratio of 1:5. The mass concentration of the hydrogen peroxide solution is 20%. The obtained mixture is dried and placed in a tubular furnace. It is pyrolyzed at 550°C for 60 min to obtain the target sludge biochar.

[0030] (2) The sludge biochar is mixed with electrolytic manganese slag, silicon-aluminum coupled solid waste and alkaline activated active materials and stirred to solidify / stabilize the electrolytic manganese slag.

[0031] Comparative Example 1 A sludge biochar-based binder for solidifying / stabilizing electrolytic manganese slag, the formula is 90% silicon-aluminum coupling solid waste, 5% sludge biochar, and 5% alkaline excitation active material; wherein the silicon-aluminum coupling solid waste is a mixture of incineration slag, nepheline tailings, ceramic slurry, and red mud in a mass ratio of 4:2:1:3, the alkaline excitation active material is carbide slag and sodium metaaluminate, the mixing ratio is 6:4, the surfactant is sodium dodecylaminopropionate, and the ratio of alkaline excitation active material to surfactant is 7:3. The preparation method is:

[0032] (1) First, the iron content of the selected original sludge is less than 20%. The sludge is dried at 100-105°C, ground by a planetary vibration mill and passed through a 200-mesh sieve. The treated dry sludge is placed in a tubular furnace and pyrolyzed at 550°C for 80 min to obtain original biochar. The prepared original sludge biochar is evenly mixed with a hydrogen peroxide solution at a mass ratio of 1:5. The concentration of the hydrogen peroxide solution is 20%. The obtained mixture is dried and placed in a tubular furnace. It is pyrolyzed at 550°C for 60 min to obtain the target sludge biochar.

[0033] (2) The sludge biochar is mixed with electrolytic manganese slag, silicon-aluminum coupled solid waste and alkaline activated active materials and stirred to solidify / stabilize the electrolytic manganese slag.

[0034] Comparative Example 2 A sludge biochar-based binder for solidifying / stabilizing electrolytic manganese slag, the formula of which is 95% silicon-aluminum coupling solid waste, 0% sludge biochar, and 5% alkaline activating active material; wherein the silicon-aluminum coupling solid waste is a mixture of incineration furnace slag, nepheline tailings, ceramic mud, and red mud in a mass ratio of 4:2:1:3, the alkaline activating active material is carbide slag and sodium aluminate in a mixing ratio of 6:4, the surfactant is sodium dodecylaminopropionate, and the ratio of the alkaline activating active material to the surfactant is 7:3.

[0035] The preparation method is the same as Example 2.

[0036] Results detection: The sludge biochar-based binder prepared in the above examples and comparative examples was used to solidify the electrolytic manganese slag to obtain a solidified body, and the solidified body was subjected to toxic leaching according to the National Standard of the People's Republic of China HJ557-2010 "Toxicity leaching method for solid waste leaching - horizontal oscillation method", and the results are shown in Table 2; According to the national standard of the People's Republic of China GB11911-89 "Determination of iron and manganese in water by flame atomic absorption spectrophotometry", Mn in the leaching solution was determined. 2+ The leaching concentration results are shown in Table 2.

[0037] Table 2 Performance parameters of the cured product

[0038] As shown in Table 2, the biochar-based binder solidified body Mn prepared in Example 1 2+ The leaching concentration is the lowest, which meets the requirements of the National Standard of the People's Republic of China GB8978-1996 "Comprehensive Wastewater Discharge Standard" for Mn in surface water. 2+ The requirement of content is ≤2mg / L.

Claims

1. A sludge biochar-based binder for solidifying / stabilizing electrolytic manganese slag, characterized by: The binder is prepared by mixing sludge biochar, silicon-aluminum coupling solid waste and alkali-activated active material. In the mixed ingredients, by weight percentage, silicon-aluminum coupling solid waste accounts for 77%-90%, sludge biochar accounts for 5-20%, and alkaline-activated active material accounts for 3-5%.

2. The sludge biochar-based binder for solidifying / stabilizing electrolytic manganese slag according to claim 1, characterized in that: The sludge biochar is prepared by the following steps: drying and grinding the iron-rich municipal sludge, pyrolyzing it at 550-650°C for 80-120 minutes to obtain the original biochar, adding hydrogen peroxide solution to the original biochar, stirring until the mixture is uniformly mixed, drying the obtained mixture, and pyrolyzing it again at 550-650°C for 80-120 minutes to prepare the sludge biochar.

3. The sludge biochar-based binder for solidifying / stabilizing electrolytic manganese slag according to claim 2, characterized in that: The iron-rich municipal sludge has an iron content of 20-30%; The mass ratio of the original biochar to the hydrogen peroxide solution is 1:5-10, and the mass concentration of the hydrogen peroxide solution is 10-30%.

4. The sludge biochar-based binder for solidifying / stabilizing electrolytic manganese slag according to claim 1, characterized in that: The silicon-aluminum coupling solid waste is a mixture of two or more of incineration slag, nepheline tailings, ceramic slurry, construction waste residue and red mud, which are mixed and calcined at 800-900° C. for 1-2 hours.

5. The sludge biochar-based binder for solidifying / stabilizing electrolytic manganese slag according to claim 1, characterized in that: The alkaline excitation active material comprises 70%-80% of an alkaline excitation material and 20-30% of a surfactant by weight percentage, wherein the alkaline excitation material comprises one or more of carbide slag, sodium aluminate, and sodium hydroxide, and the surfactant comprises one or more of sodium dodecylaminopropionate, alkyl dimethyl sulfoethyl betaine, and alkyl dimethyl hydroxypropyl phosphate betaine.

6. A method for solidifying / stabilizing electrolytic manganese slag with a sludge biochar-based binder as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: The sludge biochar is mixed with electrolytic manganese slag, silicon-aluminum coupling solid waste and alkaline-activated active materials and stirred to obtain a sludge biochar-based binder of solidified / stabilized electrolytic manganese slag.

7. The method according to claim 6, characterized in that: The electrolytic manganese slag is original electrolytic manganese slag with a moisture content of 10-16%. It is crushed and sieved. In terms of weight percentage, the electrolytic manganese slag accounts for 60-70% of the total amount of the sludge biochar-based binder.